Völkerrechtliche Jurisdiktionsgrundlagen für den Datenschutz im Netz - Herrmann, Stefan (Mohr Siebeck, 2021)
Stefan Herrmann examines the permissibility and limitation of cross-border data protection regulation issues on the internet from an international law perspective and demonstrates how regulatory conflicts can be dealt with.
PublicationDate: 20210317
Keywords: extraterritorial -- Territorialitätsprinzip -- Anerkennung von Vollstreckungsmaßnahmen -- Wirkungsprinzip -- Recht auf Vergessenwerden, -- Jurisdiktionskonflikt -- regulatory pay cap -- Völkerrecht -- Europarecht